Liferaft Operating Procedures as A Support For Crew Safety In KM. Mulya Sentosa II - A Agus Tjahjono; Dian Yasinta Tasin; Lusda Mulia Tidarriski (IWJ : Inland Waterways Journal, 2023)
Liferaft is a safety device on a ship in the form of a boat equipped with a roof in the form of a tent and inside there are tools to survive in an emergency. The purpose of this study was to determine the factors that caused the lack of understanding of the operating procedures of the liferaft in KM. Mulya Sentosa II, to determine the effect of a lack of understanding of optimal liferaft operating procedures on the MV. Mulya Sentosa II. The results showed that the factors causing the lack of understanding of the optimal operation of the liferaft in KM. Mulya sentosa II is the lack of implementation of emergency drills, the absence of information in written form regarding the procedures for operating the liferaft , the lack of responsibility for the Deck Officers for the implementation of the exercise and the lack of information on the procedures for operating safety equipment, especially regarding the liferaft on board the ship in accordance with the provisions or guidelines that have been set, giving strict sanctions to Deck Officers, and providing information in written form regarding the procedures for operating the liferaft properly and optimally and then posting it in a place that is reached by all ship crews.